Detection of intramyocardially injected DiR-labeled mesenchymal stem cells by optical and optoacoustic tomography - Markus T. Berninger (Photoacoustics, 2017)
The distribution of intramyocardially injected rabbit MSCs, labeled with the near-infrared dye 1,1′-dioctadecyl-3,3,3′,3′-tetramethylindotricarbo-cyanine-iodide (DiR) using hybrid Fluorescence Molecular Tomography-X-ray Computed Tomography (FMT-XCT) and Multispectral Optoacoustic Tomography (MSOT) imaging technologies, was investigated. Viability and induction of apoptosis of DiR labeled MSCs were assessed by XTT- and Caspase-3/-7-testing in vitro. 2 × 106, 2 × 105 and 2 × 104 MSCs labeled with 5 and 10 μg DiR/ml were injected into fresh frozen rabbit hearts. FMT-XCT, MSOT and fluorescence cryosection imaging were performed. Concentrations up to 10 μg DiR/ml did not cause apoptosis in vitro (p > 0.05). FMT and MSOT imaging of labeled MSCs led to a strong signal. The imaging modalities highlighted a difference in cell distribution and concentration correlated to the number of injected cells. Ex-vivo cryosectioning confirmed the molecular fluorescence signal. FMT and MSOT are sensitive imaging techniques offering high-anatomic resolution in terms of detection and distribution of intramyocardially injected stem cells in a rabbit model.